2016
DOI: 10.1177/0146645316630167
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the environment in existing exposure situations

Abstract: Abstract-The International Commission on Radiological Protection (ICRP) described its approach to the protection of the environment and how it should be applied in Publication 124. The report expanded on the Commission's objectives for environmental protection, and how the Derived Consideration Reference Levels (DCRLs) apply within different exposure situations. DCRLs relate radiation effects to doses over and above their normal local background radiation levels, and consider different potential pathways of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…A number of potential case studies covering the three exposure situations have been identified, including those described in Copplestone et al (2016): Andreeva Bay waste storage site remediation, Little Forest radioactive waste burial ground, and impact of Mayak releases along the Techa river. Additionally, the radium and uranium contaminated sites (at Winterbeek in Belgium, Gunnar, and Midwest uranium mine and mill sites), former weapons testing sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of potential case studies covering the three exposure situations have been identified, including those described in Copplestone et al (2016): Andreeva Bay waste storage site remediation, Little Forest radioactive waste burial ground, and impact of Mayak releases along the Techa river. Additionally, the radium and uranium contaminated sites (at Winterbeek in Belgium, Gunnar, and Midwest uranium mine and mill sites), former weapons testing sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Copplestone et al (2016) explored several case studies to determine what might happen when considering the environment and, more specifically, non-human biota ICRP 2017 Proceedings…”
mentioning
confidence: 99%
“…The facility was licensed as a 'prescribed legacy site' under the ARPANS Act in July 2016, becoming the first site licensed under this new classification, and is an example of an existing exposure situation under regulatory control. The LFLS was presented as a case study at the ICRP symposium in 2015 (Copplestone et al, 2016). As noted by Copplestone et al, assessments of the potential impacts on humans and wildlife applied the ICRP recommendations and the International Basic Safety Standards requirements for existing exposure situations.…”
Section: Case Study 4: Little Forest Legacy Sitementioning
confidence: 99%
“…Indeed, the systems for protection of people and for protection of the environment can be used in an integrated manner -when warranted -to protect people and the environment. While protection of people is the primary concern in most situations, certain scenarios may benefit from an integrated approach; other situations may require decisions based solely on environmental considerations (Copplestone, 2012;Pentreath, 2012b;ICRP, 2014;Pentreath et al, 2015;Copplestone et al, 2016).…”
Section: Elements Of the Icrp Environmental Protection Systemmentioning
confidence: 99%
“…Furthermore, the ongoing update of the IAEA generic models for assessing the impact of radioactive discharges (IAEA, 2001) is providing examples of planned exposure situations. Copplestone et al (2016) provided examples of case studies and sites available for studies of environmental protection under emergency and existing exposure situations. Key messages to date state that such exposure scenarios require site-specific decisions, and that sometimes both humans and biota need to be considered when developing the management strategy.…”
Section: Further Development Of the System For Application In Specifimentioning
confidence: 99%